2016
DOI: 10.1111/ijsa.12138
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination due to Ethnicity and Gender: How susceptible are video‐based job interviews?

Abstract: Fairness toward job applicants differing in gender and ethnicity in a video‐based assessment interview was explored. For this purpose, 103 female and 105 male participants, including 38 who declared to have a migration background of their own, rated a behavior anchored rating scale after having watched the videotaped answers of a potential applicant. The domains assessed were communication skills and the capacity to work in a team. The videos of the applicants were generated with the help of standardized scrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This alone can be seen as a significant fairness advantage over traditional interviewing techniques. Personal bias toward interviewees can be further reduced when combined with computational approaches [28] and video-based communication [29]. Virtual reality and other digital environments have been successfully deployed for training purposes, particularly for effective interview preparation.…”
Section: Discussionmentioning
confidence: 99%
“…This alone can be seen as a significant fairness advantage over traditional interviewing techniques. Personal bias toward interviewees can be further reduced when combined with computational approaches [28] and video-based communication [29]. Virtual reality and other digital environments have been successfully deployed for training purposes, particularly for effective interview preparation.…”
Section: Discussionmentioning
confidence: 99%
“…However, literature has shown that factors such as gender, ethnicity, physical appearance or obesity do have an influence, even though taking a decision on these factors is expressly forbidden by law in both Europe and the United States [6]. Moreover, in the context of AVIs, having access to the image of the candidates early in the selection process has a potential impact on increasing the influence of aesthetics [7], gender or ethnicity of the candidates [8]. Approaches to mitigate discrimination in job interviews may differ from country to country [9].…”
Section: A Discrimination In Job Interviewsmentioning
confidence: 99%
“…Dimensions such as anxiety, self-efficacy, its predictive validity, performance outcome, and the impact of age, accent, age, and gender, were previously investigated [10,11]. Moreover, it was shown that anchoring-and-adjuments heuristics and associated motivational mechanisms drive bias against stigmatized people in interview decisions [12].…”
Section: Introductionmentioning
confidence: 99%